A comparison study of intraocular pressure measurements between goldman applanation tonometer and non-contact air-puff tonometer - ديب مريم; تيم درويش; قحطان جلول (Latakia University Journal -Medical Sciences Series, 2022)
Objective: To compare intraocular pressure measurements(Iop) between Goldman applanation tonometer(GAT) and Non-contact Air-puff tonometer(AP). Subjects and Methods: This study was carried out at 242 eyes of 121 subjects attending outpatient clinic of Ophthalmology at Tishreen university hospital from 2021-2022. All participants underwent a complete ophthalmological examination including Autorefractomy, Central corneal thickness, microscopic biological fundoscopy and intraocular pressure measurement by Non-contact Air-puff tonometer (where we obtained 3 values and calculated the mean of them) then Goldmann applanation measure. The subjects’ ages ranged between 20 to 60 years old with mean 39.7+_12.3. Results : The readings obtained by AP tonometer were higher than those obtained by GAT, and this difference was most obvious when the GAT measurement of Iop exceeded 14 mmHg.No statistically significant variation in Iop measurements was noted between devices when the subjects’ age and sex were considered. There was a significant association between NCTdifferences and (CCT) . Conclusion : There is a significant difference in the measurements of Iop between GATs and AP tonometer and measurements of Iop by AP tonometer are usually higher than those obtained by GAT regardless of the subjects’ age and sex . However , this difference increase with increased CCT.